Fuel-cell power conversion system based on double dual topologies. (15th August 2022) - Garza-Arias, Enrique; Valdez-Resendiz, Jesus E.; Rosas-Caro, Julio C.; Mayo-Maldonado, Jonathan C.; Sanchez, Victor M.; Escobar, Gerardo; Rodriguez, Alma; Rodrigo, Pedro M.
Abstract: This article describes (and demonstrates through experiments) the feasible implementation of a power conversion system designed for a Fuel Cell (FC) application in renewable energy generation. The system is designed to be powered by an FC stack, which output is a low (in amplitude) non-regulated dc voltage, with a relatively wide range of variation. The system must boost the voltage from the power source to an internal 200 V dc bus, while the final output voltage (after the inversion) must be provided at a level of 120 V ac. The main feature of the described system is that it is based on double-dual converters, a family of converters with several advantages such as automatic power balance and large voltage gain; this leads to a good performance and power quality. The system is based on a double dual boost converter to increase and regulate the dc-voltage, and a double dual buck converter, to invert the dc-voltage and provide an ac-voltage as output. The article shows the system's feasibility through theoretical analysis and provides experimental results with an FC stack. Experimental results are provided to demonstrate the feasibility of the proposed system. Highlights: A power conversion system for a PEMFC application is presented. The power conversion system is based on double-dual converters which provide automatic power balance and large voltage gains. A double-dual boost converter is used to increase and regulate the dc-voltage of the PEMFC stack. The AC-voltage output of the power conversion system is provided by a double-dual buck converter. Experimental results are shown to demonstrate the feasibility of the double dual boost converters for PEMFC applications.